(untitled) (Research, Society and Development, 2022)
This study aims to understand the socio-emotional impact and coping strategies experienced by the nursing team working in the Intensive Care Unit (ICU) during the COVID-19 pandemic. This is a qualitative, descriptive and exploratory research. Data collection took place through audio-recorded semi-structured interviews, and interpretation was based on the inductive thematic analysis, based on the theoretical study that disagrees about the mental health reference of Brazilian nursing professionals in the face of the pandemic. Twenty-eight professionals participated: eight management nurses, seven assistant nurses and 13 nursing technicians. Based on the responses, three categories and 14 subcategories were created, namely: Category 1: Remarkable stories and subcategories: the rare highs; family members hospitalized in the same ICU; the last words. Category 2: Socio-emotional impact and subcategories: fear of contamination; stiffening of feelings and the automatism of work; anxiety, tiredness and stress; sensitivity and empathy; emotional shock and hopelessness. Category 3: Coping strategies and subcategories: emotional empowerment and self-care; psychological and psychiatric follow-up; segregation of personal and professional life; support networks: co-workers and family members; deprivation of external information and spirituality and religiosity. The nursing team suffered relevant socio-emotional impacts resulting from the COVID-19 pandemic. Thus, the establishment of socio-emotional quality is essential, especially as a coping strategy, with a view to protecting health and preventing injuries for these professionals, even after the pandemic.